Actual and symbolic prisons, Black men, and the freedom-unfreedom paradox: interrogating the bad faith of racialized oppression in a post-accountable United States - Smith, Darron T.; Harris, Brenda G. (Frontiers in Psychology, 2023)
Drawing on systemic racism theory, White racial framing and the notion of bad faith as the connecting, justifying thread between ideals of freedom and equality and actions realizing unfreedom and inequities, this essay explores the alchemy of race, masculinity, and racialized oppression and its consequences for Black men past and present in U.S. society. This essay’s aim is to trace the historical ideologies and cultural practices, relations, and normative standards that have contributed to, and hence must be challenged to confront, the inequitable, race-based relations of power and privilege at the root of institutionalized injustices. To do so, this essay interrogates the dissonance of bad faith as a corrective mode of truth telling to highlight and tap the equity potential of Black men’s collective, historical rejections of the White mainstreams’s conflicting definitions and deceptive reasonings requisite for pushing toward racial justice, healing, and peace.